Male‐to‐female gender dysphoria: Gender‐specific differences in resting‐state networks. Issue 5 (5th April 2017) - Clemens, Benjamin; Junger, Jessica; Pauly, Katharina; Neulen, Josef; Neuschaefer‐Rube, Christiane; Frölich, Dirk; Mingoia, Gianluca; Derntl, Birgit; Habel, Ute
Abstract: Introduction: Recent research found gender‐related differences in resting‐state functional connectivity (rs‐FC) measured by functional magnetic resonance imaging (fMRI). To the best of our knowledge, there are no studies examining the differences in rs‐FC between men, women, and individuals who report a discrepancy between their anatomical sex and their gender identity, i.e. gender dysphoria (GD). Methods: To address this important issue, we present the first fMRI study systematically investigating the differences in typical resting‐state networks (RSNs) and hormonal treatment effects in 26 male‐to‐female GD individuals (MtFs) compared with 19 men and 20 women. Results: Differences between male and female control groups were found only in the auditory RSN, whereas differences between both control groups and MtFs were found in the auditory and fronto‐parietal RSNs, including both primary sensory areas (e.g. calcarine gyrus) and higher order cognitive areas such as the middle and posterior cingulate and dorsomedial prefrontal cortex. Overall, differences in MtFs compared with men and women were more pronounced before cross‐sex hormonal treatment. Interestingly, rs‐FC between MtFs and women did not differ significantly after treatment. When comparing hormonally untreated and treated MtFs, we found differences in connectivity of the calcarine gyrus and thalamus in the context of the auditory network, as well as the inferior frontal gyrus in context of the fronto‐parietal network. Conclusion: Our results provide first evidence that MtFs exhibit patterns of rs‐FC which are different from both their assigned and their aspired gender, indicating an intermediate position between the two sexes. We suggest that the present study constitutes a starting point for future research designed to clarify whether the brains of individuals with GD are more similar to their assigned or their aspired gender. Abstract : Recent research found gender‐related differences in resting‐state functional connectivity (rs‐FC) measured by functional magnetic resonance imaging (fMRI). To the best of our knowledge, there are no studies examining differences in rs‐FC between men, women, and individuals who report a discrepancy between their anatomical sex and their gender identity, i.e. gender dysphoria (GD). To address this important issue, we present the first fMRI study systematically investigating differences in typical resting‐state networks (RSNs) and hormonal treatment effects in 26 male‐to‐female GD individuals (MtFs) compared with 19 men and 20 women. Our results provide first evidence that MtFs exhibit patterns of resting‐state functional connectivity which are different from both their assigned and their aspired gender, indicating an intermediate position between the two sexes.